2021
DOI: 10.1038/s41598-021-81132-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of subject-specific adaptive mechanical loading for bone healing in a mouse tail vertebral defect

Abstract: Methods to repair bone defects arising from trauma, resection, or disease, continue to be sought after. Cyclic mechanical loading is well established to influence bone (re)modelling activity, in which bone formation and resorption are correlated to micro-scale strain. Based on this, the application of mechanical stimulation across a bone defect could improve healing. However, if ignoring the mechanical integrity of defected bone, loading regimes have a high potential to either cause damage or be ineffective. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 700 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…We addressed this by using our recently developed RTFE based loading approach 26 , which takes into account the individual strain distribution within the callus for determining individual loading settings at weekly post-operative intervals. In a recent study by Malhotra et al 27 individualized cyclic mechanical loading (week 0 – week 4, 3x/week) was shown to significantly increase bone volume fraction in a partial vertebral defect model compared to controls. So far, no study using a complete defect model assessed the effect of local cyclic mechanical loading (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…We addressed this by using our recently developed RTFE based loading approach 26 , which takes into account the individual strain distribution within the callus for determining individual loading settings at weekly post-operative intervals. In a recent study by Malhotra et al 27 individualized cyclic mechanical loading (week 0 – week 4, 3x/week) was shown to significantly increase bone volume fraction in a partial vertebral defect model compared to controls. So far, no study using a complete defect model assessed the effect of local cyclic mechanical loading (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…According to previous work, SED was used as a mechanical signal (Christen et al, 2012(Christen et al, , 2013(Christen et al, , 2014. More recent studies (né Betts et al, 2020;Malhotra et al, 2021) have identified an effective strain as a preferred candidate for bone mechanoregulation analysis using multidensity FE analysis. However, previous research has shown that these signals are strongly correlated (Pistoia et al, 2002;Ruimerman et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, complementary methods have been proposed to computationally monitor 3D bone microstructure changes over time (time-lapse) and calculate local mechanical loading using micro-finite element (micro-FE) analysis. This has been demonstrated in mice (Schulte et al, 2013;né Betts et al, 2020;Malhotra et al, 2021) and patients (Christen et al, 2014;Mancuso and Troy, 2020) at such high spatial resolution that cellular behaviour-in the form of bone remodelling sites-can be studied and the corresponding mechanical loading can be calculated. Subsequently, these methods can be used to investigate bone's underlying mechanoregulated remodelling process, which may be the key to the development of patient-specific therapeutic or pharmacological interventions for various bone diseases.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…More recently, complementary methods have been proposed to computationally monitor 3D bone microstructure changes over time (time-lapse) and calculate local mechanical loading using microfinite element (micro-FE) analysis. This has been demonstrated in mice (Schulte et al, 2013;né Betts et al, 2020;Malhotra et al, 2021) and patients (Christen et al, 2014;Mancuso and Troy, 2020) at such high spatial resolution that cellular behaviour -in the form of bone remodelling sites -can be studied and the corresponding mechanical loading can be calculated. Subsequently, these methods can be used to investigate bone's underlying mechanoregulated remodelling process, which may be the key to the development of patient-specific therapeutic or pharmacological interventions for various bone diseases.…”
Section: Introductionmentioning
confidence: 97%